Does right ventricular function predict survival in patients with chronic obstructive lung disease?. Issue 8 (August 1988) - France, A J; Prescott, R J; Biernacki, W; Muir, A L; MacNee, W
Abstract : Non-invasive measurements of the right ventricular ejection fraction by radionuclide ventriculography were made in 115 patients with chronic obstructive lung disease. Survival was assessed over a mean period of 918 days. The right ventricular ejection fraction was reasonably normal in most patients (mean 0.42, range 0.10-0.66) but was lower in those with peripheral oedema, indicating cor pulmonale (mean 0.31 (SD 0.07); p less than 0.0001). Right ventricular ejection fraction was related to survival, but the relationship was weak (p = 0.03) by comparison with the association between the arterial oxygen and carbon dioxide tensions and survival (both p less than 0.0001). It is concluded that, although right ventricular function is predictive of survival in patients with chronic obstructive lung disease, it is probably a reflection of severity of disease and does not directly affect the prognosis.